A STUDY OF PLASMA MAGNESIUM CONCENTRATIONS AND THEIR RELATIONSHIP WITH ANEMIA AND HEMODIALYSIS DURATION IN PATIENTS WITH END-STAGE CHRONIC KIDNEY DISEASE (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate plasma magnesium (Mg) concentrations and analyze their association with selected clinical and paraclinical characteristics in end-stage chronic kidney disease (CKD) patients undergoing hemodialysis (HD). Methods: A cross-sectional descriptive study was conducted on 100 CKD patients receiving HD at Military Hospital 103. Plasma Mg concentrations were measured using an automated clinical chemistry system (Beckman Coulter, USA). Results: The group with hemoglobin (HGB) ≥ 100 g/L had higher Mg concentrations than the group with HGB < 100 g/L (p = 0.039). A reduced plasma Mg concentration was observed in 16.7% of patients in the HD ≥ 12 months group, compared with 0% in the HD < 12 months group. The HD ≥ 12 months group had a higher prevalence of elevated Mg than the HD < 12 months group (21.8% versus 13.6%). There was an association between HD duration and the overall rate of abnormal plasma Mg concentrations (p = 0.045). Plasma Mg concentration was not associated with clinical symptoms such as pallor of skin and mucosa, edema, pruritus, fatigue, nor with erythrocyte indices including RBC, HGB, HCT, MCV, MCH, and MCHC. Conclusion: In end-stage CKD patients on HD, plasma Mg concentration is positively associated with the degree of anemia. The prevalence of abnormal plasma Mg concentrations was significantly higher in the HD ≥ 12 months group compared with the HD < 12 months group (38.5% versus 15.6%).
Keywords: Magnesium, clinical characteristics, paraclinical features, end-stage chronic kidney disease, hemodialysis.